The Effects of Chromium Complex and Level on Glucose Metabolism and Memory Acquisition in Rats Fed High-Fat Diet - Şahin, Kazım; Tuzcu, Mehmet; Orhan, Cemal; Agca, Can A.; Şahin, Nurhan; Guvenc, Mehmet; Hayirli, Armagan (Humana Press Inc, 2011)
Conditions in which glucose metabolism is impaired due to insulin resistance are associated with memory impairment. It was hypothesized that supplemental chromium (Cr) may alleviate insulin resistance in type 2 diabetes and consequently improve memory acquisition, depending upon its source and level. In a complete randomized design experiment, male Wistar rats (n = 60; weighing 200-220 g) were fed either normal (8%, normal diet (ND)) or high-fat (40%, high-fat diet (HFD)) diet and supplemented with Cr as either chromium-glycinate (CrGly) or chromium-acetate (CrAc) at doses of 0, 40, or 80 mu g/kg body weight (BW) via drinking water from 8 to 20 weeks of age. Feeding HFD induced type 2 diabetes, as reflected by greater glucose/insulin ratio (2.98 vs. 2.74) comparing to feeding ND. Moreover, HFD rats had greater BW (314 vs. 279 g) and less serum (53 vs. 68 mu g/L) and brain (14 vs. 24 ng/g) Cr concentrations than ND rats. High-fat diet caused a 32% reduction in expressions of glucose transporters 1 and 3 (GLUTs) in brain tissue and a 27% reduction in mean percentage time spent in the target quadrant and a 38% increase in spatial memory acquisition phase (SMAP) compared with ND. Compared with supplemental Cr as CrAc, CrGly was more effective to ameliorate response variables (i.e., restoration of tissue Cr concentration, enhancement of cerebral GLUTs expressions, and reduction of the glucose/insulin ratio and SMAP) in a dose-response manner, especially in rats fed HFD. Supplemental Cr as CrGly may have therapeutic potential to enhance insulin action and alleviate memory acquisition in a dose-dependent manner, through restoring tissue Cr reserve and enhancing cerebral GLUTs expressions.
Keywords: Chromium-glycinate; Chromium-acetate; High-fat diet; Type 2 diabetes; Insulin resistance; Learning performance